A wideband dual‐circularly polarized 2 × 1 array antenna using multi‐layer substrate for compact structure. Issue 1 (30th September 2019) - Rahman, Muhammad Asad; Nishiyama, Eisuke; Toyoda, Ichihiko
Abstract: A novel compact dual‐circularly polarized (CP) 2 × 1 microstrip array antenna with wideband characteristic is proposed. The antenna is realized using multi‐layer technique. The antenna consists of two orthogonally fed patch elements integrated with a 90° branch‐line coupler for achieving dual‐CP operation. The complete feed network, inspired by double‐sided MIC technology, is designed using microstrip lines and slot lines distributed in different three metal layers. ±90° out‐of‐phase signals caused by the branch‐line coupler are combined with two orthogonal feed lines of the patches to excite right‐hand circular polarization (RHCP) or left‐hand circular polarization (LHCP). More than 40% size reduction is achieved by employing multilayer structure instead of single‐layer structure. The measured 3‐dB axial ratio bandwidths of RHCP/LHCP are 8.31/10.19%. Peak gain is more than 9 dBic with good CP radiation performance. The antenna performance is validated by measured data.